Optimalisasi Kinerja Alat Pengering Pengolahan Makanan Bahan Dasar Pisang pada Kelompok Usaha Khadijah Food di Nagari Ladang Laweh Kab.Agam - Alfitri, Nadia; Azra, Tuti; Kurniadi, Dedi; Anton, Anton; Yefriadi, Yefriadi (Pengelola Jurnal Politeknik Negeri Ketapang Jl. Rangga Sentap, Dalong Sukaharja, Ketapang 78813. Telp. (0534) 3030686 Kalimantan Barat, 2025)
Khadijah Food are experiencing obstacles related to the Banana Sale production process which still uses traditional methods in drying raw materials through direct sunlight. Actually, this partner already has an oven dryer, but the performance of the tool is not optimal because the production results and the quality of the dried bananas are not as expected, because the caramelization process, which is an important stage in drying bananas, does not go well. The solution provided is to use a food drying device using the concept of drying moisture content with a heating element for drying, and a blower for heat circulation in the drying room, so that the drying results of bananas can run more optimally because apart from the heat from the heater, sufficient air circulation is also provided in the drying process. Drying banana ingredients with a concept like this will allow the caramelization stage to run optimally because the water content will not be trapped on the surface of the banana or evaporate. Caramelization is a reaction of sugar content to high heat temperatures which results in bananas becoming more pliable or not easily brittle, brownish in color and having a distinctive taste. With this service activity, partners benefit directly through the touch of technology provided. An increase in turnover will occur and market needs will also be met even though the weather is not supportive.